QRS-T Angle Predicts Cardiac Risk and Correlates With Global Longitudinal Strain in Prevalent Hemodialysis Patients - Skampardoni, Sofia; Green, Darren; Hnatkova, Katerina; Malik, Marek; Kalra, Philip A.; Poulikakos, Dimitrios (Frontiers in Physiology, 2019)
Background: Cardiovascular disease is the commonest cause of death in hemodialysis (HD) patients but accurate risk prediction is lacking. The spatial QRS – T angle is a promising electrophysiological marker for sudden cardiac death risk stratification. The aim of this study was to assess the prognostic value of spatial QRS-T angle derived from standard 12 lead electrocardiograms (ECG) and its association with echocardiographic parameters in HD patients. Methods: This prospective study of 178 prevalent HD patients (aged 67±14 years, 72% men) collected ECG and echocardiographic data on an annual basis. Baseline echocardiograms at study entry were used for cross-sectional comparisons with ECGs. Study endpoints were all-cause mortality, cardiovascular mortality, and major adverse cardiac events (MACE). The QRS – T angle was calculated from standard 10-second ECG as the total cosine R to T (TCRT) using singular value decomposition and expressed in degrees. TCRT above 100° was defined as abnormal. Results: During a follow-up period of 36 ± 19 months, 74 patients died, including 17 cardiac deaths, and 54 suffered from MACE. In multivariate Cox regression analysis, QRS-T angle by TCRT at baseline was associated with increased cardiovascular mortality both as a continuous value and dichotomised below or above 100° (HR 1.016, p=0.029, CI: 1.002-1.030 and HR 3.506, CI: 1.118-10.995, p=0.031 respectively) and with MACE dichotomised at 100° (HR 1.902, CI: 1.046-3.459; p=0.035). In multivariate regression analysis including baseline parameters, echocardiographic global longitudinal strain (GLS) was significantly correlated with TCRT (F 9.648, r2=0.192, beta=0.331, t=4.4429, CI: 1.976-5.157, p<0.001). Conclusion: TCRT correlates with GLS and is independently associated with cardiac deaths and MACE in HD patients.